An effective control algorithm for dynamic voltage restorer under symmetrical and asymmetrical grid voltage conditions - A. Boussaid (National Technical University "Kharkiv Polytechnic Institute", 2021)
Introduction. Voltage sag, which is associated to a transitory drop in the root mean square voltage characterizing an electrical source network. During these perturbations, the corresponding electronic customers and devices will suffer from serious operating troubles causing dangerous damages. Purpose. In order to attenuate this disturbance effects, the Controlled Dynamic Voltage Restorer constitutes a very interesting solution among many others that have been proposed. The novelty of the proposed work consists in presenting an enhanced algorithm to control efficiently the dynamic voltage restorer when voltage sag is suddenly occurred. Methods. The proposed algorithm is based on an instantaneous phase locked loop using a multi variable filter to synthesize unitary signals involved in compensation voltages computation relative to the sag apparition. Practical value. A detailed study concerning typical voltage sag, which is consolidated by simulation and experimental results, is conducted to show the used algorithm’s effectiveness to cancel the corresponding voltage sag.